Effects of Commutative Heat Stress on Immunoresponses in Broiler Chickens Reared in Closed System - Zahraa,; Al-Ghamdi, H. (International Journal of Poultry Science, 2008)
Eastern region of Saudi Arabia was characterized by high temperatures especially in summer season, so this study was carried out to investigate effect of heat stress on immunoresponse in broiler chickens kept in a closed system. Thirty Cobb 500 chicken (22-day-old) were exposed to 40 °C/4 hrs/day for ten days. Blood samples were collected before and after heat exposure at 3 stages during experimental, (1st, 5th and 10th day) samples which were taken at the first day before heat exposure were served as control group (Basal level). The result revealed that heat stress led to significant (p < 0.01) decrease in plasma ascorbic acid, Antibodies (IgG and IgM) levels in all stage, whereas percentage lymphocyte and heterophil and H/L ratio showed significant changes during three stage of experiment. It is suggested that alteration of plasma ascorbic acid and immunoresponse may reflect heat stress in chicken.